1989
DOI: 10.1136/ard.48.5.396
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, biochemical, and radiographic effects of aminohydroxypropylidene bisphosphonate treatment in rheumatoid arthritis.

Abstract: SUMMARY A placebo controlled, double blind study of aminohydroxypropylidene bisphosphonate (APD), given by monthly intravenous infusion, was conducted in 40 patients with rheumatoid arthritis. Biochemical markers of increased bone resorption, such as fasting urinary calcium/ creatinine ratio and hydroxyproline/creatinine ratio, were suppressed significantly in the APD group to approximately 50% and 60% of the pretreatment level respectively, and serum calcium fell transiently after the first APD infusion. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 16 publications
1
38
0
2
Order By: Relevance
“…Therefore, the contrast between the sup- AA, adjuvant-induced arthritis; CA, collagen-induced arthritis; RA, rheumatoid arthritis; E, effective; NE, not effective; W, worsening. References: (1) Francis et al, 1972;(2) Flora, 1979;(3) Babier et al, 1986;(4) Francis et al, 1989;(5) Nugent et al, 1993;(6) Dunn et al, 1993a;(7) Markusse et al, 1990;(8) Ralston et al, 1989;(9) Tan et al, 1989;(10) Bijvoet et al, 1980;(11) Maccagno et al, 1994; (12) present results. pressive effect of non-aminoBPs and the ineffectiveness of aminoBPs on arthritis cannot be attributable to effects on bone resorption.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Therefore, the contrast between the sup- AA, adjuvant-induced arthritis; CA, collagen-induced arthritis; RA, rheumatoid arthritis; E, effective; NE, not effective; W, worsening. References: (1) Francis et al, 1972;(2) Flora, 1979;(3) Babier et al, 1986;(4) Francis et al, 1989;(5) Nugent et al, 1993;(6) Dunn et al, 1993a;(7) Markusse et al, 1990;(8) Ralston et al, 1989;(9) Tan et al, 1989;(10) Bijvoet et al, 1980;(11) Maccagno et al, 1994; (12) present results. pressive effect of non-aminoBPs and the ineffectiveness of aminoBPs on arthritis cannot be attributable to effects on bone resorption.…”
Section: Discussionmentioning
confidence: 71%
“…Ralston et al (1989) and Tan et al (1989) have found that it is not effective in restricting the progression of periarticular bone erosion, although the bone resorption was suppressed. These results seem to be in agreement with those of our animal experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous trials in patients with RA have demonstrated the beneficial effects of oral or parental bisphosphonates in preventing the progression of generalized skeletal bone loss and stabilizing systemic bone mass. Despite their success in preventing systemic bone loss, however, trials with bisphosphonates in patients with RA have not demonstrated efficacy with respect to attenuating the progression of focal bone erosions (6)(7)(8)(9)(10). In contrast, results of studies in several different animal models of inflammatory arthritis indicate that bisphosphonate treatment can produce beneficial effects in both systemic bone loss and progression of focal bone erosions (3,(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Jarette et al [37] reported preliminary evidence that treatment with zoledronic acid plus methotrexate showed better results in reducing bone destruction than methotrexate alone. However, many other studies have failed to show positive effects of bisphosphonates against bone destruction in RA [38][39][40] . This may be because, in these studies, the treatment was initiated too late or the strength of the bisphosphonates used was not enough to treat the bone destruction in RA.…”
Section: Resultsmentioning
confidence: 99%